The witch of Willow Hall - Fox, Hester (Graydon House, 2018)
"In the wake of a scandal, the Montrose family and their three daughters--Catherine, Lydia and Emeline--flee Boston for their new country home, Willow Hall.The estate seems sleepy and idyllic. But a subtle menace creeps into the atmosphere, remnants of a dark history that call to Lydia, and to the youngest, Emeline. All three daughters will be irrevocably changed by what follows, but none more than Lydia, who must draw on a power she never knew she possessed if she wants to protect those she loves"--